Termorregulação e desempenho fisiológico de Thorapa taophora (Anura: Cycloramphidae) - Silva, Antonio Carlos Gallo da [UNIFESP] (2015)
Ectotherms must regulate body tempetarute inside a tolerable range of temperature to optmize physiological functions. In this context, behavioural thermoregulation is an important strategy for metabolic compensation. Shifts in thermal performances curves have been described for species inhabiting environments with different thermal variability and must be related to adaptation in an evolutionary sense. We proposed to investigate how populations inhabiting environments with different thermal variability modulate the thermoregulatory capacity and physiology to cope with environmental temperature. For this we selected four populations of Thoropa taophora tadpoles where two populations inhabit rock seashores (high thermal variability - beach) and the other two inhabit waterfall rock shores (low thermal variability - forest). We mesured body temperature and operative temperature on natural microhabitat and collected the prefered temperature using a thermal gradiente to analyze the thermoregulatory capacity by the index E=1-(dc/do). We assayed lactate dehydrogenase (LDH) and citrate synthase (CS) thermal sensitivity and mesured locomotor performance against temperature for each population to investigate how temperature affects physiological performances. From each performance curve we collected the speed maximum temperature value (Vmax) and Vmax 80% temperature (B80min e B80max). Thermoregulatory capacity were moderate in one of the beaches (beach 1: E=0.37±0.15) compared to the others (beach 2: E=-0.08±0.15; forest 1: E=0.4±0.1; and forest 2: E=-0.02±0.1; mean±s.d.; ANOVA: F3,37=34.694, p<0.001). LDH and CS thermal sensibility were different among populations (LDH: beach 1: 3.5±0.3; beach 2: 5.3±0.7; forest 1: 3.7±0.8; forest 2: 2.3±0.4; ANOVA: F3,19=23.14, p<0.001; CS: beach 1: 2.5±0.7; beach 2: 1.4±0.3; forest 1: 2.4±0.6; forest 2: 2.3±0.7; mean±s.d.; ANOVA F3,20=3.84, p<0.05;). Populations from beach environments had bigger B80min, B80max and Vmax temperature values compared with forest populations (Vmax: beach 1: 32.75±0.16; beach 2: 25.70±0.46; forest 1: 20.29 ± 1.21; forest 2: 20.90±1.02; ANOVA: F3,2615=15,065, p<0.001; B80min: beach 1: 27.42±0.11; beach 2: 21.32±0.15; forest 1: 17.06±0.53; forest 2: 17.11±0.64; ANOVA: F3,2615=41,714, p<0.001; B80max: beach 1: 34.71±0.26; beach 2: 32.25±0.61; forest 1: 26.79±0.30; forest 2: 27.74±0.20; ANOVA: F3,2615=5,739, p<0.001; mean±s.d. ?C). Thus T. taophora tadpoles from beach environments have a better thermoregulatory capacity, a higher enzymatic thermal sensibility and shifts for higher temperaturas in thermal performance curves compared to tadpoles from forest environments.